How Does Listening to “Fetal Heartbeats” Affect the Feelings of Pregnant Women? - Beksac, Mehmet Sinan; Unal, Canan; Yalaniz, Burcu; Cagan, Murat; Tanacan, Atakan; Fadiloglu, Erdem; Donmez, Hanife Guler (Gynecology Obstetrics & Reproductive Medicine, 2024)
OBJECTIVES: This study was conducted to evaluate the impact of listening to fetal heartbeats (FHBs) on the feelings of normal and high-risk pregnancies (HRPs), and to learn the colors and geometrical figures representing their feelings. STUDY DESIGN: This retrospective cohort study consisted of 291 pregnant women who applied for a non-stress test (NST). Participants were divided into two groups; 1: Normal pregnancies (Group1) and 2: HRPs (Group2). Demographic variables, feelings in response to listening to FHBs (negative, neutral, positive), grade mark (0-10) of feelings, color (warm, neutral, cold), and figure (simple, complex) preferences were retrospectively evaluated. RESULTS: Of the 291 women, 172 (59.1%) Group 1 participants were compared to 119 (40.9%) Group 2 participants. Group 1 and Group 2 had similar feelings (p>0.05), however, the rate of negative feelings was higher in Group 2 (11.6% vs. 20.2%). Higher marks were observed in Group 2 with happiness and peace/relaxation after listening to FHBs. Fear was the lowest mark in women with positive/neutral feelings in both groups. Women in Group 1 preferred warm colors regardless of their feelings. Women in Group 2 who have positive feelings chose warm colors, whereas women who felt neutral or negative more commonly chose cold (55.5%) and neutral (41.7%) colors (p=0.017). Independent of feelings, simple figures were predominately preferred (p=0.04). CONCLUSION: NST is more than a perinatal surveillance method and listening to FHBs has a positive impact on the feelings of pregnancies. Warm colors were commonly related to positive feelings. Simple figures were preferred regardless of feelings.